(untitled) (Research, Society and Development, 2022)
The quality of life of health professionals was hypothetically reflected during the pandemic. Therefore, the objective of this study is to evaluate the impacts on the quality of life of health professionals who act/acted on the front line in the COVID-19 pandemic in the municipality of Santarém-Pará.The research is classified as quantitative, descriptive and cross-sectional, it was carried out with health professionals who act/acted on the front line in the COVID-19 pandemic, assessing the positivity of these professionals for COVID-19, whether they needed to be hospitalized and/or had post-COVID symptoms, using a specific form, and quality of life using the WHOQOL-bref questionnaire. 46 professionals participated in the survey, in which they answered questions about contamination, hospitalization and whether they had post-COVID symptoms, through which it was possible to verify that most professionals were contaminated, but did not need to be hospitalized. In the analysis of quality of life, it was identified that the environment domain of the WHOQOL-bref, a low score was obtained. Thus, even with a small sample, frontline professionals have a quality of life that is “neither good nor bad”, even in the face of a sudden change in the routine of the work environment, as well as even being infected, there were no complications that would make them feel sick. if hospitalization.